2001
DOI: 10.1046/j.0960-7692.2001.00500.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ‘pattern recognition’ and logistic regression models for discrimination between benign and malignant pelvic masses: a prospective cross validation

Abstract: Results Pattern recognition performed better than the two logistic regression models (sensitivity around 85%, specificity around 90%). Using a risk of malignancy of > 50% to indicate malignancy (as suggested in the original publications), the sensitivity of the Tailor model was 69% and the specificity 88% (n = 133). The corresponding values for the Timmerman model were 62% and 79% (n = 82). The receiver operating characteristics curves showed the two logistic regression models to have similar diagnostic proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
147
2
13

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(166 citation statements)
references
References 16 publications
4
147
2
13
Order By: Relevance
“…Unfortunately, when tested prospectively, most models did worse than in the studies where they had been created, and they did not achieve the performance of experienced sonologists using subjective assessment of the ultrasound image (4,(15)(16)(17)(18). The Royal College of Obstetricians and Gynecologists (19) and a recent review article by Geomini and colleagues (20) recommend the risk of malignancy index (RMI; ref.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, when tested prospectively, most models did worse than in the studies where they had been created, and they did not achieve the performance of experienced sonologists using subjective assessment of the ultrasound image (4,(15)(16)(17)(18). The Royal College of Obstetricians and Gynecologists (19) and a recent review article by Geomini and colleagues (20) recommend the risk of malignancy index (RMI; ref.…”
Section: Introductionmentioning
confidence: 99%
“…18 However, when the diagnostic performance of risk-stratification models are compared to "pattern recognition" (i.e., subjective evaluation of grayscale and Doppler flow features), the latter is found to perform better, yielding a sensitivity of around 85% and specificity of around 90%. 19 In our study, ultrasonological morphology was found to be accurate in 100% cases that were detected prior to surgery.…”
Section: Discussionmentioning
confidence: 84%
“…Sonography alone is highly sensitive in detection of ovarian mass malignancy, but its specificity is relatively low (Valentin, 2001;Diamandis, 2003;Valentin, 2004;Enakpene, 2009 DOI:http://dx.doi.org/10.7314/APJCP.2012.13.8.4199 Ovarian Malignancy Prediction Models Based on Age Sonographic and Serum CA125 serum CA125 measurement is a specific test in prediction of ovarian malignancy (Edgell, 2010).…”
Section: Discussionmentioning
confidence: 99%